Efforts to Increase the Benefits of Spatial Planning in the Planning Mechanism of Development Programs in Batu Bara Regency - Tavy Juanda; Abdi Sugiarto (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study aims to examine Efforts to Increase the Benefits of Spatial Planning in the Development Program Planning Mechanism in Batu Bara Regency This research is a qualitative research with a descriptive approach that seeks to present the concept of implementation in development planning in connection with the quality of regional development planning. Data collection techniques are the means used to obtain the data and information needed to achieve research objectives. Data analysis is a process or effort to process data obtained from the results of interviews, field notes and documentation, into new information so that the characteristics of the data are good. The results of the research on efforts to increase the benefits of the Spatial Plan (RTR) in the planning mechanism of development programs in Batu Bara Regency must prioritize synchronization between spatial planning and integrated and sustainable development policies. The main steps that need to be taken include aligning the RTR with the RPJMD, developing infrastructure according to zoning, and strengthening regulations and spatial supervision. In addition, the use of GIS technology for monitoring and involvement of the community and the private sector in planning is also very important. Through the implementation of a targeted RTR, Batu Bara Regency can optimally maximize the potential of its area, including industrial, tourism, and agricultural areas. Thus, the benefits of RTR can be realized in the form of more inclusive, environmentally friendly development, and support the economic welfare of the community and regional sustainability.